STRATEGI PENGEMBANGAN INDUSTRI ALAT BERAT DI BALI (STUDI KASUS CV. DANA KARYA) - I Made Chandra Mandira; Gusti Agung Ayu Putu Cahya Damayanti (Journal Publicuho, 2023)
This study aims to develop a marketing strategy that can be applied to heavy equipment rental CV. Dana Karya in order to survive from similar competitors. The research method uses mixed methods with an exploratory research approach. Data collection techniques were carried out by means of interviews, questionnaires and documentation which were tested using technical triangulation. Informants were obtained through purposive sampling technique as many as 7 people, namely, company owners, employees and customers. This study was analyzed using the SWOT analysis technique using weights, ratings on IFAS and EFAS calculations which were then analyzed using the business life cycle. The results of this study indicate that the company's position obtained from the results of the total score of IFAS and EFAS is in quadrant 1 by implementing an aggressive growth strategy (growth-oriented strategy) that focuses on SO (Strength – Opportunities) strategy by utilizing all of the company's internal strengths to seize and take advantage of opportunities externally as much as possible. Based on the classification of internal - external factors, it is obtained that the IE matrix which is in cell 1 shows CV. Dana Karya is in a growth and build position. In relation to the business life cycle, the position of CV's heavy equipment rental business can be identified. CV. Dana Karya is currently in the growth phase.